1998
DOI: 10.1093/mutage/13.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Spindle poisons can induce polyploidy by mitotic slippage and micronucleate mononucleates in the cytokinesis-block assay

Abstract: The human in vitro cytokinesis-blocked micronucleus (MN) assay has been extensively used for detection of clastogenic and aneugenic agents. In this test binucleate cells are generally considered to be the main target cell population for assessing genotoxic effect and almost no attention is paid to the biological information contained in mono-nucleate cells. In this study we analysed the frequencies of micronucleate mononucleates in a control population and after in vitro exposure to clastogens or aneugens. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Microtubule poisoning initially results in a G2/M arrest, where activation of the spindle assembly checkpoint prevents progression through mitosis [31]. However, cancer cells are frequently able to adapt and undergo mitotic slippage out of G2/M arrest [32]. While cells which possess wild type p53 can subsequently arrest at G0/G1 post mitotic slippage, a response that is mediated by p21/WAF1 [33], cells lacking functional p53 are thought to continue synthesizing DNA after mitotic slippage without cytokinesis, resulting in polyploidy [34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule poisoning initially results in a G2/M arrest, where activation of the spindle assembly checkpoint prevents progression through mitosis [31]. However, cancer cells are frequently able to adapt and undergo mitotic slippage out of G2/M arrest [32]. While cells which possess wild type p53 can subsequently arrest at G0/G1 post mitotic slippage, a response that is mediated by p21/WAF1 [33], cells lacking functional p53 are thought to continue synthesizing DNA after mitotic slippage without cytokinesis, resulting in polyploidy [34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Polyploidy (an increase in the sets of chromosomes) and multinucleation are characteristic features of mitotic slippage. Tetraploidy, or successive polyploidizaton if these cells undergo successive cell cycles, was first described by early studies that sought to correlate polyploidy, micronuclei and cell survival following exposure to nocodazole (Elhajouji et al 1998, Decordier et al 2008.…”
Section: Polyploidy Multinucleation and Chemoresistancementioning
confidence: 99%
“…The use of Cyt‐B limits scoring of MN to once‐divided BN cells and avoids the scoring of spurious MN that may appear from a number of confounding factors such as less than optimal cell culture conditions and altered cell division kinetics 5. However, it has been demonstrated that noncytokinesis‐blocked versions of the assay can identify statistically significant increases in MN among aneugens which arise from the phenomenon of mitotic slippage 6, 7, 8. Therefore, it is often necessary to perform the assay both in the presence and absence of Cyt‐B, which increases the number of samples that must be evaluated.…”
Section: Introductionmentioning
confidence: 99%